Effects of Alcohol on the Human Vision System - Farrow, L.A (Canadian Journal of Optometry, 2021)
Alcohol and alcoholism affects us in many ways. It affects the social and economic fabric of our society, the physiology of the human body, and perhaps most importantly, the effectiveness of the mental processing of the human mind.